2020
DOI: 10.3390/molecules25122738
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Aspects of Local Anesthetics

Abstract: Thanks to the progress made in chemical technology (particularly in the methodologies of stereoselective syntheses and analyses) along with regulatory measures, the number of new chiral drugs registered in the form of pure enantiomers has increased over the past decade. In addition, the pharmacological and pharmacokinetic properties of the individual enantiomers of already-introduced racemic drugs are being re-examined. The use of the pure enantiomer of a drug that has been used to date in the form of a racema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Lidocaine is a local anesthetic drug derived from cocaine, and widely used in clinical application such as anti-bacteria, antiinflammation, local skin anesthesia and so on (Caracas et al, 2009;Adler et al, 2017;Cizmarikova et al, 2020). An increasing number of evidences have demonstrated that lidocaine could affect the development of multiple tumors including ovarian and breast cancer (Gao et al, 2018;Khan et al, 2019;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Lidocaine is a local anesthetic drug derived from cocaine, and widely used in clinical application such as anti-bacteria, antiinflammation, local skin anesthesia and so on (Caracas et al, 2009;Adler et al, 2017;Cizmarikova et al, 2020). An increasing number of evidences have demonstrated that lidocaine could affect the development of multiple tumors including ovarian and breast cancer (Gao et al, 2018;Khan et al, 2019;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The separation was initially developed on a 50.2 cm x 50 μm fused silica capillary, investigating the effects of the pH, the concentration of BGE components (buffering agent, cationic additives) and TM-β-CD on the migration time and resolution R S of the Ibu enantiomers. R S was calculated according to the equation R S = 1.18 × (t m1 − t m2 ) / w 0.5(1) + w 0.5 (2) (1…”
Section: Methods Developmentmentioning
confidence: 99%
“…The analytical methods to monitor the pharmacokinetics of local anesthetics were recently reviewed [ 6 ]. The changes in the pure enantiomers for different anesthetics, such as bupivacaine, mepivacaine, prilocaine, and ropivacaine, were studied.…”
Section: Chiral Analysis In Pharmacokineticsmentioning
confidence: 99%
“…In the case of LC, several CSPs based on cyclodextrins, macrocyclic antibiotics, or substituted carbamates from cellulose and amylose were tested. It was concluded that although the use of local anesthetics in an enantiomerically pure form has advantageous properties in terms of its activity and lowtoxicity, its potential has not yet been fully studied and verified [ 6 ]. The enantioselective methods to study pharmacokinetics and pharmaceutical formulations of venlafaxine were also recently revised, which encompass LC-UV, LC-MS, LC-MS/MS, and capillary electrophoresis methods [ 44 ].…”
Section: Chiral Analysis In Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation